Reaktualisasi Hadis Walimah sebagai Respons terhadap Fenomena Fear of Missing Out (FOMO) Pernikahan Modern: Reactualizing the Hadith of Walimah as a Response to the Fear of Missing Out (FOMO) Phenomenon in Modern Weddings - Ahmad Jaya Ramadhani; Moch Irfan Hakim; Muhid; Khotimah Suryani (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study aims to analyze the influence of Fear of Missing Out (FOMO) on the practice of walimah in modern weddings, examine the concept of walimah based on hadith in a contextual perspective, and formulate efforts to actualize these values in contemporary life. This research employs a qualitative approach using library research, with descriptive-analytical methods applied to hadith texts on walimah derived from classical hadith collections as well as relevant academic literature on FOMO and modern marriage. The findings reveal that FOMO, driven by social media exposure, has shifted the meaning of walimah from a religious practice rooted in gratitude and simplicity into a form of social representation characterized by consumerism and public validation. In contrast, hadiths on walimah emphasize principles of simplicity, flexibility, and blessing as the foundation of its implementation. Therefore, the reactualization of walimah hadith is essential to restore the orientation of marriage toward its substantive values, independent of digital social standards. This study highlights that a contextual understanding of hadith can serve as a relevant approach to addressing contemporary social challenges while maintaining the essence of Islamic teachings in modern wedding practices.